Empirical shear based model for predicting plate end debonding in FRP strengthened RC beams - El-Sayed, Ahmed K.; Al-Saawani, Mohammed A.; Al-Negheimish, Abdulaziz I. (Journal of Civil Engineering and Management, 2021)
This paper presents the development of a simplified model for predicting plate end (PE) debonding capacity of reinforced concrete (RC) beams flexurally strengthened using fiber reinforced polymers (FRP). The proposed model is based on the concrete shear strength of the beams considering main parameters known to affect the opening of the shear cracks and consequently affect PE debonding. The model considers also the effect of the location of the cut-off point of FRP plate along the span of the beam. The proposed model was verified against experimental database of 128 FRP-strengthened beams collected from previous studies that failed in PE debonding. In addition, the predictions of the proposed model were also compared with those of the existing PE debonding models. The predictions of the model were found to be comparable to the best predictions provided by the existing models, yet the proposed model is simpler. Furthermore, the proposed model was combined with the ACI 440 IC debonding equation to provide a procedure for predicting the governing debonding failure mode in FRP strengthened RC beams. The procedure was validated against 238 beam tests available in the literature, and shown to be a reliable approach.